The effects of education levels of developmental care in Australia: Perceptions and challenges. Issue 4 (July 2021) - Griffiths, Nadine; Spence, Kaye; Galea, Claire; Psaila, Kim; Foureur, Maralyn; Sinclair, Lynn
Abstract: Background: Developmental care consists of a range of clinical, infant-focused, and family-focused interventions designed to modify the neonatal intensive care environment and caregiving practices to reduce stressors on the developing brain. Since the inception of developmental care in the early 1980s, it has been recommended and adopted globally as a component of routine practice for neonatal care. Despite its application for almost 40 y, little is known of the attitude of neonatal nurses in Australia towards the intervention. Aims and objectives: The objective of this study was to establish Australian neonatal nurse perceptions of developmental care and explore associations between developmental care education levels of the nurses and personal beliefs in the application of developmental care. Design: This involves a cross-sectional survey design. Methods: An online questionnaire was completed by 171 neonatal nurses. Participants were members of the Australian College of Neonatal Nursing (n = 783). Covariate associations between key components of developmental care and respondents' geographical location, place of employment, professional qualifications, and developmental care education level were analysed. The reporting of this study is in accordance with the Enhancing the Quality and Transparency of Health Research Checklist for Reporting Results of Internet E-Surveys. Results: Differences were observed between groups for geographical location, place of employment, and professional qualification level. Rural nurses were less likely to support the provision of skin-to-skin care (odds ratio [OR]: 0.6, 95% confidence interval [CI ]: 0.2–1.8) than nurses in a metropolitsan unit. Nurses working in a neonatal intensive care unit and nurses with postgraduate qualifications were more likely to support parental involvement in care ([OR: 2.3, 95% CI : 0.9–6.2] and [OR: 2.1, 95% CI : 0.6–7.4], respectively). Rural respondents were more likely to have attended off-site education (OR: 3.6, 95% CI: 1.3–9.9) than metropolitan respondents. Conclusion: The application of developmental care in Australia may be influenced by inadequate resources and inequitable access to educational resources, and similar challenges have been reported in other countries. Overcoming the challenges requires a focused education strategy and support within and beyond the neonatal intensive care unit.